The Compartmentalization of Amyloid-β in Idiopathic Normal Pressure Hydrocephalus Brain Biopsies - Libard, Sylwia; Hodik, Monika; Cesarini, Kristina Giuliana; Dragomir, Anca; Alafuzoff, Irina (Journal of Alzheimer's disease, 2024)
Background: Amyloid-β (Aβ) is one of the hallmark lesions of Alzheimer’s disease (AD). During the disease process, Aβ undergoes biochemical changes, producing toxic Aβ variants, proposed to be detected within the neurons. Idiopathic normal pressure hydrocephalus (iNPH) causes cognitive impairment, gait, and urinary symptoms in elderly, that can be reversed by a ventriculo-peritoneal shunt. Majority of iNPH subjects display different Aβ variants in their brain biopsies, obtained during shunting. Objective: To study the cellular compartmentalization of different Aβ variants in brain biopsies from iNPH subjects. Methods: We studied the cellular localization of different proteoforms of Aβ using antibodies towards different amino acid sequences or post-translational modifications of Aβ, including clones 4G8, 6F/3D, unmodified- (7H3D6), pyroglutamylated- (N3pE), phosphorylated-(1E4E11) Aβ and Aβ protein precursor (AβPP), in brain biopsies from 3 iNPH subjects, using immunohistochemistry and light microscopy (LM), light microscopy on semi-thin sections (LMst), and electron microscopy (EM). Results: In LM all Aβ variants were detected. In LMst and EM, the Aβ 4G8, 6F/3D, and the pyroglutamylated Aβ were detected. The AβPP was visualized by all methods. The Aβ labelling was located extracellularly with no specific signal within the intracellular compartment, whereas the AβPP was seen both intra- and extracellularly. Conclusions: The Aβ markers displayed extracellular localization when visualized by three assessment techniques, reflecting the pathological extracellular accumulation of Aβ in the human brain. No intracellular Aβ pathology was seen. AβPP was visualized in intra- and extracellularly, which corresponds to the localization of the protein in the membranes of cells and organelles.